Adaptation to multifocal and monovision contact lens correction - Fernandes, Paulo Rodrigues (2013)
Purpose. To compare visual performance with the Biofinity multifocal (MF) contact lens with monovision (MV) with the Biofinity single-vision contact lens. Methods. A crossover study of 20 presbyopic patients was conducted. Patients were randomized first into either an MF or an MV lens for 15 days for each modality, with a washout period between each lens type. Measurements included monocular and binocular high- and low-contrast logarithm of the minimum angle of resolution visual acuity (VA) at distance and near visions, binocular distance contrast sensitivity function, and near stereoacuity. Results. At 15 days, patients lost fewer than two letters (half a line of VA) of binocular distance and near VA, with the MF and MV lens under high- and low-contrast conditions (P 9 0.05 for both comparisons). No statistically significant differences were seen in binocular VA at near or distance with either lens. However, the monocular distance VA improved significantly in the nondominant eye, with the MF lens by one line over the 15-day period under high-contrast (P = 0.023) and lowcontrast (P = 0.035) conditions; this effect was not seen with the MV lens. Contrast sensitivity function was within the normal limits with both lenses. The stereoacuity was significantly (P G 0.01) better with MF than with MV. Conclusions. Multifocal contact lens correction provided satisfactory levels of VA comparable with MV without compromising stereoacuity in this crossover study. The near vision significantly improved in the dominant eye, and the distance vision improved in the nondominant eye from 1 to 15 days with the MF lens, suggesting that patients adapted to the multifocality overtime, whereas this was not true for MV. (Optom Vis Sci 2013;90:228Y235)